(untitled) (Annals of Medical Research, 2021)
Aim: Only a few studies have investigated the comorbid headache in children with tic disorders (TD). In this study, thus, we aimed to examine the frequency and clinical correlates of comorbid headache in TD.Material and Methods: The sample consisted of 98 children and adolescents aged 6–16 years with a diagnosis of any tic disorder and 108 healthy children and adolescents matched for age, gender and sociocultural characteristics. All participants underwent a semi-structured psychiatric interview to establish a psychiatric diagnosis. The diagnosis of headache was made according to the third edition of the International Classification of Headache Disorders criteria. Also, a specially prepared personal information sheet and Yale Global Tic Severity Scale were applied.Results: Children and adolescents with TD had a significantly higher frequency of headache compared to those in the control group (44.9% vs. 22.2%, p=0.001). The most common type of headache in both groups was migraine. We determined that the rate of diagnosis of chronic tic disorders, percentage of the presence of vocal tics, severity of tics, the proportion of patients taking pharmacotherapy for tics, and the rate of psychiatric comorbidity were significantly higher in patients with a headache than those without headache.Conclusion: The results of our study confirm studies showing suggesting a possible relationship between TD and headache, and supports the proposition that headache is a comorbidity of TD. However, further studies exploring the mechanisms of this relationship are required. It also would be advisable to screen children with TD in terms of headaches.